Novel Sources of Fetal Stem Cells for Future Regenerative Medicine - Yani Lina; Andi Wijaya (The Indonesian Biomedical Journal, 2012)
BACKGROUND: Mesenchymal stromal cells are multipotent cells considered to be of great promise for use in regenerative medicine. However, the cell dose may be a critical factor in many clinical conditions and the yield resulting from the ex vivo expansion of mesenchymal stromal cells derived from bone marrow may be insufficient. Thus, alternative sources of mesenchymal stromal cells need to be explored.CONTENT: There are multiple extra-embryonic tissues emerging during gestation including umbilical cord blood (UCB), amniotic fluid (AF), Wharton’s jelly, the amniotic membrane and the placenta, which are all discarded following birth. Fetal stem cells from these sources actually represent a new class of stem cells developmentally and operationally located between the state of embryonic stem cells and adult stem cells, sharing and exhibiting features of pluripotency and multipotency, without necessarily implying that they can generate every type of tissue.SUMMARY: Fetal stem cells have been recently isolated from several tissues (amniotic fluid, umbilical cord, Wharton’s jelly, amnion and placenta). They are derived either from the fetus proper or from the supportive extra-embryonic structures. They represent ideal sources for regenerative medicine since they are easily accessible, exhibit high proliferation rates, do not form teratomas and present no ethical reservations like embryonic stem cells (ESC). Their functional features indicate that they actually represent intermediates between ESC and adult stem cells.KEYWORDS: mesenchymal stem cells, fetal stem cells, amniotic fluid, umbilical cord, placenta, wharton’s jelly